Wokół "kompleksu wypędzenia". Polska debata historyczna w pierwszej dekadzie po przełomie w stosunkach bilateralnych - Ruchniewicz, Małgorzata (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2021)
The political breakthrough in Polish–German relations in 1989/1990 resulted in sparking discussion on important issues concerning forced migrations in Europe in the20 th century – namely, displacement of Germans from the lands incorporated into Poland in 1945. Research on this problem in Poland and divided Germany, limited by political factors in the first 40 postwar years, could be undertaken in full extent and in collaboration only after the fall of communism.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne